TINDAK TUTUR EKSPRESIF MARIO TEGUH DALAM ACARA “GOLDEN WAYS” - Wulandari .; Agustina .; Ngusman . (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: This study aims to describe the types, strategies and situation context of expressive speech act used by Mario Teguh in Golden Ways program. This research uses a qualitative descrtive method. Data collection was done downloading Mario Teguh video recording of Mario Teguh’s speech act in Golden Ways program on Metro TV through site www.metrotvnew.com. Based on the research findings, we can conclude the following three things. First, the types of expressive speech act used by Mario Teguh in Golden Ways program, showing gratitude, congratulating, complimenting, criticizing, apologizing. The finding showed that complimenting is the most dominant expressive speech act used by Mario Teguh. As a motivator, he should try to cheer the audiences up so that his intention can be accepted by them. Moreover, it will increase the rating of this program. Second, speech strategies used by Mario Teguh in Golden Ways program, speaking in what it is without a word, speaking with a word of positive politeness, speaking with a word of negative politeness, off record speech. Based on findings, the most dominant strategy used is speaking with a word of positive politeness since Mario Teguh tried to cheer the audiences up by exalting audiences of actual fact so that either opinion or critics conveyed can be accepted by them. Third, speech situation context found in Mario Teguh Golden Ways program. The context of using speech strategy in what it is without a word tended to be used on situation the situation of younger audiences, sensitive subject (-K +Sst), speech strategy with a word of positive politeness is used on situation the situation of younger audiences, sensitive subject (-K+Sst), speech strategy with a word of negative politeness is used on situation the situation of younger audiences, insensitive subject (-K-Sst), and off record speech strategy tended to be used on situation the situation of younger audiences, insensitive subject (-K –Sst). Kata Kunci: Tindak tutur ekspresif, Golden Ways